Effect of S SMILE Instructional Model based on Contemplative Education for Enhancing Nursing Student’s 5 Skills subject to Thai Qualifications Frame Work for Higher Education - Rattanawumol, Cathareeya; Wannapornsiri , Chommanard; Petcharat, Manika; Khamboon, Thidarat; Longchoopol, Chaowanee; Wongchanhan, Kamonroj; Ruetrakul, Jirarat (Journal of The Royal Thai Army Nurses, 2020)
This research is a quasi-experimental study, one group pre-test post-test design, with an aim to investigate the effects of the application of S SMILE Model based on contemplative education for enhancing nursing student’s 5 skills subject to Thai Qualifications Framework for Higher Education. The sample group included 80 first-year nursing students in the Faculty of Nursing Naresuan University who had enrolled the course “Humanized Nursing Care”. The research instruments consisted of 1) Experimental tool which was the instructional model “S SMILE Model” based on contemplative education comprising 6 components as follows: 1) Space 2) Self-reflection 3) Meditation 4) Integral Life Practice 5) Listen Actively and 6) Evaluation 2) Data collecting tools were questionnaire for evaluating 5 skills subject to Thai Qualifications Framework for Higher Education and questionnaire for assessing satisfaction toward given instructional model. Statistics used for data analysis included percentage, mean, standard deviation, t-test. The research findings suggested that by applying the instructional model, post-test scores for nursing student’s 5 skills subject to Thai Qualifications Framework for Higher Education were significantly higher than that of pre-studying ones at statistical significance of 0.001 while satisfaction score was significantly above the required level with statistical significance of .001.